1989
DOI: 10.1002/ar.1092240108
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of thymocyte attachment to thymus stromal cells in culture by using phase‐contrast and scanning electron microscopy

Abstract: Direct cellular contact between thymocytes and thymus stromal cells within the thymus appears to contribute to the maturation of thymocytes. Thymocyte-stromal cell complexes, formed in vivo, have been isolated by others and postulated to play a role in T-cell differentiation. These previous studies have been hampered, however, by a time-consuming isolation procedure from which only small numbers of these complexes are recovered. We have examined a model to study thymocyte-stromal cell complexes in vitro in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The ultrastructure of the binding site indicated closely apposed membranes of both cells (data not shown). This finding may suggest the presence of specific receptors for cellular recognition and binding between thymocytes and TEL-2 cells (LaRochelle and Jones, 1989). A noticeable property of the cultures of TEL-2 cells was that they formed numerous "round spaces."…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The ultrastructure of the binding site indicated closely apposed membranes of both cells (data not shown). This finding may suggest the presence of specific receptors for cellular recognition and binding between thymocytes and TEL-2 cells (LaRochelle and Jones, 1989). A noticeable property of the cultures of TEL-2 cells was that they formed numerous "round spaces."…”
Section: Discussionmentioning
confidence: 96%
“…Rapid intercellular adhesion seems to be common in the cellular interaction of thymocytes and thymic stro-ma1 elements (LaRochelle and Jones, 1989). Many thymocytes became attached to the surface of the TEL-2 cells shortly after cocultivation.…”
Section: Discussionmentioning
confidence: 99%
“…In a follow-up study with SEM and transmission electron microscopy (TEM), Hirata et al (1991) have shown that as an initial event for the process of the selective elimination of DP thymocytes from the culture, the attachment between the thymocyte and TEL-2 cell leads to a migration of thymocytes between the TEL-2 processes. Similar cellular interactions between thymocytes and thymic stromal elements have been described in vitro (LaRochelle and Jones, 1989). It is, however, still open to question concerning the cytological events which occur as a sequelae of the initial attachment.…”
mentioning
confidence: 57%
“…7d), followed the ingestion of thymocytes by TEL-2 cells. The ultrastructure of these binding sites may suggest the presence of specific receptors for cellular recognition between thymocytes and thymus stromal cells (TEL-2 cells) (LaRochelle and Jones, 1989;Hirata et al, 1991).…”
Section: Prominent Membrane Events Between the Phase Of Attachment Anmentioning
confidence: 99%